Potential Analysis and Optimization of Combined Cooling, Heating, and Power (CCHP) Systems for Eco-Campus Design Based on Comprehensive Performance Assessment - Liu, Zhonghui; Gao, Weijun; Qian, Fanyue; Zhang, Liting; Kuroki, Soichiro (Frontiers in Energy Research, 2021)
At present, countries all around the world have implemented energy-saving and emission reduction measures to achieve carbon neutralization. The combined cooling, heating, and power (CCHP) system is a high-efficiency energy system that can promote energy-saving and decrease carbon emissions. The choices of installed capacity and operation strategies impacts the economy, energy-saving, and environmental protection of combined cooling, heating, and power systems. The aim of this study was to determine the potential and comprehensive benefits of combined cooling, heating, and power systems based on the comprehensive performance assessment. In this study, a comprehensive performance index (CPI) method was presented to optimize the configurations and operation strategies of combined cooling, heating, and power systems in a Japan eco-campus, based on historically monitored data. According to the influencing factors of the combined cooling, heating, and power system in comprehensive performance index evaluation, the adaptability and development potential of economy, energy saving, and CO2 emission reduction were evaluated to consider future renovation of energy systems. In this study, we adopted a seasonal time-of-use (STOU) electricity price to evaluate the economic performance of combined cooling, heating, and power systems and compared them to the time-of-use (TOU) electricity price. The results indicated that the seasonal time-of-use electricity price was more economic in regions that had high cooling demand in summer. By comparing the CO2 emission coefficient of electricity in different regions in Japan, we could estimate that more than 40% of the cleaner energy ratio was positive. The results obtained can provide suggestions for the future development of combined cooling, heating, and power systems.